Gob-side entry retaining formed by roof cutting without roadside support. (2018) - Yin, Dawei; Meng, Xiangxi; Zhang, Zhaoyi; Liu, Baocheng
When using gob-side entry retaining (GSER) under hard-roof conditions, the roadside support deforms and destroys easily due to the great overburden stress induced by the large length and time of the hanging roof. Selecting the 20196 working face in the Linhua coal mine located in western China as an example, the technology of GSER formed by roof cutting without roadside support (RCWRS) is studied. The overlying strata movement characteristics, support system of the surrounding rocks, and pre-splitting construction technique are developed. And stress transfer and bearing of the hanging roof structure above retaining roadway are discussed. The deformation of surrounding rocks of the retaining roadway is also monitored. The engineering application shows that this technology can ensure the stability of the retaining roadway. The maximum roof subsidence is 172 mm, the maximum floor heave is 37 mm, and the coalside deformation is 56 mm. The above observations are significant for coal mining under hard-roof conditions. [Received: May 24, 2017; Accepted: December 4, 2017]